Octa-n-butyl-1κ 2 C,2κ 2 C,3κ 2 C,4κ 2 C-tetrakis(μ-2-hydroxybenzoato)-1:2κ 2 O:O;2:3κ2 O:O′;3:4κ 2 O:O;1:4κ 2 O:O′-di-μ 3-oxido-1:2:3κ 3 O:O:O;1:3:4κ 3 O:O:O-tetratin(IV) - Reisi, Reza; Shahirin, Siti Munirah; Misran, Misni; Lo, Kong Mun; Ng, Seik Weng (International Union of Crystallography, 2008)
In the centrosymmetric tetranuclear title compound, [Sn4(C4H9)8(C7H5O3)4O2], one of the two independent Sn atoms is five-coordinate in a cis-C2SnO3 trigonal-bipyramidal geometry [C—Sn—C = 142.7 (1)°]; the geometry is distorted owing to a long Sn⋯O(double bond) interaction [Sn⋯O = 2.862 (1) Å]. The other Sn atom has a bent R 2Sn skeleton [C—Sn—C = 144.0 (1)°], but the geometry is best regarded as being a trans-C2SnO4 octahedron as the Sn–O(single bond) interaction is shorter [Sn—O = 2.674 (1) Å].